Screening for aneuploidies by maternal age, fetal nuchal translucency and maternal serum biochemistry at 11-13+6 gestational weeks - Karadžov-Orlić Nataša (Srpski Arhiv za Celokupno Lekarstvo, 2012)
Introduction. Aneuploidies are the major cause of perinatal death and early psychophysical disorders. Objective. In this study, we analyzed detection and false-positive rates of screening for aneuploidies in the first trimester by the combination of maternal age, fetal nuchal translucency (NT) thickness and maternal serum free beta-human chorionic gonadotrophin (β-hCG), and pregnancy-associated plasma protein-A (PAPP-A) at 11-13+6 weeks of gestation, using the appropriate software developed by the Fetal Medicine Foundation. Methods. Our screening study for aneuploidies analyzed 4172 singleton pregnancies from January 2006 to December 2010. The sensitivities and false-positive rates using the combined aneuploidies determination for the risk cut-off of 1:275 were evaluated. Results. In the trisomy 21 pregnancies, the fetal NT was higher than 95th centile, in 72.8%, serum free b-hCG concentration it was above the 95th centile in 55% and serum PAPP-A was below the 5th centile in 47% of the cases. In the trisomy 18 and 13, the fetal NT was above 95th centile in 66.6% and 44.4% of the cases, respectively. The serum free b-hCG concentration was above the 95th centile in 0 and 10%, but serum PAPP-A was below 5th centile in 80.9% and 88.8% of pregnancies. In the trisomy 21 pregnancies the median free beta-hCG was 2.3 MoM and the median PAPP-A was 0.45 MoM. Chromosomal abnormalities were detected in 169 fetuses: trisomy 21 (97), Turner syndrome (19), trisomy 18 (28), trisomy 13 (11) and others (14). Detection rate of combined screening for aneuploides were 86.0% with false positive rate of 5.3% (mean age 33±4.9 years, >35 years in 35% of pregnancies). Conclusion. Our study suggests that the strategy of first-trimester combined screening of biochemical values and ultrasonographic parameters at 12 gestational weeks identifies higher percentage of aneuploidies with a lower false-positive rate than a single parameter strategy.